A pH-driven method for liposomal encapsulation of dietary flavonoid rutin: Sustained release and enhanced bioefficacy. (April 2023) - Sengupta, Priti; Das, Debashree; Bhattacharya, Sampurna; Sur, Runa; Bose, Adity; Sen, Kamalika
Abstract: Dietary polyphenols offer a wide range of health benefits in functional food, nutraceutical, as well as pharmaceutical industries. Their practical applications, however, encounter several challenges due to limited solubility and bioavailability. In the present study, we have developed a pH-driven method to prepare rutin-loaded liposomes which were characterized by evaluating particle size, polydispersity index (PDI), zeta potential, TEM, and encapsulation efficacy. The IC50 value of encapsulated rutin for HeLa cells was 250 μmol/L, while free rutin shows insignificant inhibitory effect. Besides, the bioaccessibility of rutin enhanced from 9.8% to 19.7% upon liposomal encapsulation. The percentage release of free rutin in SGF and SIF was ∼98.4% and ∼98.7% respectively within 6 h. However, upon encapsulation, less than 55% was released even after 24 h. Overall, the enhanced bioaccessibility, reduced cell viability of HeLa cells, and most importantly, sustained release for rutin-loaded liposomes, accounted for the favorable outcome of our approach. Highlights: Dietary flavonoid rutin was encapsulated in liposomal bilayer using an organic solvent-free method. Sustained release effect in simulated gastric/intestinal fluid was observed for the encapsulated system. The anticancer activity of free rutin on HeLa cells was remarkably enhanced after encapsulation. The antioxidant activity of rutin was well retained even after encapsulation.